Pengaruh Model Pembelajaran Problem Based Learning dan Problem Solving Dalam Meningkatkan Keaktifan Belajar Peserta Didik Kelas V SD - Maria Novita Silalahi; Agustina Tyas Hardini (Journal on Education, 2023)
The purpose of this study was to be able to see the effect of using the Problem Based Learning and Problem Solving learning models on the learning activeness of students in thematic content of grade V elementary school. This research is included in the category of Quasi-Experimental research, the population in this study used purposive sampling technique in the experimental group of fifth grade students of SD Randuacir 01 and SD Randuacir 02 as the control group. The data collection technique in this study uses a used test by distributing questionnaires or questionnaires and tests and then the data is analyzed using SPSS Version 29 to be able to determine the effect of the two models, the researcher uses the Model Summary or simple linear regression test, the correlation or relationship value (R) is 0.663 from the output obtained the determinal coefficient (R square) of 0.440. From this explanation, it can be seen that the effect of the independent variable on the dependent variable is 44% and from the results of the research hypothesis shows that the t value is 4.189 and the sig value is 0.001 <0.05. Based on these results it can be concluded that there is a significant difference in learning activeness in the problem-based learning model with those using problem solving, in the problem-based learning model is more effective than using the problem solving learning model. This can be seen from the learning model that uses problem-based learning the highest value is 100 and the smallest is 55, while in the problem solving model the highest value is 95 and the smallest is 50.